I have gone away many times - Metileni, Moses Nzama Khaizen (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
I search for beauty and for myself amidst the debris and ruin and violence, so my poems are mainly grounded narratives that combine the lyrical and the political, celebration and lament. They reconnect with nature, the now ravaged landscapes that gave me my first impulse to make songs, poetry, and art. My poems also draw on my Xitsonga culture "“ its folklore, proverbs, idioms, parables, and clan praise songs. Stylistically I am influenced by Mahmoud Darwish's and Garcia Lorca's musical structures, while Aimé Césaire has shown me how to write a long poem in both abstract and concrete registers, and Yehuda Amichai how to write with a questioning style, dislodging accepted dogma. Local influences are Mzi Mahola and James Magaisa, with their critique and celebration of culture. I pick up fragments elsewhere, as I go.
Keywords: Uncatalogued